Site-Specific Regulation of Sulfatase and Aromatase Pathways for Estrogen Production in Endometriosis - Da Costa, Katiane de Almeida; Malvezzi, Helena; Dobo, Cristine; Neme, Rosa Maria; Filippi, Renée Zon; Aloia, Thiago Pinheiro Arrais; Prado, Elisa Rampazo; Meola, Juliana; Piccinato, Carla de Azevedo (Frontiers in Molecular Biosciences, 2022)
Endometriosis is a highly prevalent gynaecological disease characterized by lesions in different sites. Regulation of specific oestrogen pathways may favour the formation of distinct microenvironments and the progression of endometriosis. However, no study has simultaneously evaluated the gene and protein regulation of the main oestrogen-synthesising enzymes in endometriosis. Thus, our goals were to study the relationship between gene and protein expression of aromatase (CYP19A1 or ARO), steroid sulfatase (STS), and hydroxysteroid 17-beta dehydrogenase (HSD17B1) in superficial (SUP), ovarian (OMA), and deep infiltrating (DIE) endometriotic lesion sites, as well as in the eutopic endometrium of patients with (EE) and without (control) endometriosis in the same and large cohort of patients. The site-specific expression of these enzymes within different cells (glandular and stromal components) was also explored. The study included 108 patients surgically diagnosed with endometriosis who provided biopsies of EE and endometriotic lesions and 16 disease-free patients who collected normal endometrium tissue. Our results showed that CYP19A1 was detected in all endometriosis tissues and were in higher levels than in control. Unique patterns of the STS and HSD17B1 levels showed that they were most closely regulated in all tissues, with manifest greater levels in DIE compared to the other endometriotic lesion sites, OMA and SUP. Gene and protein expression of ARO, STS and HSD17B1 occurred at different rates in endometriotic sites or in EE. The distinctive levels of these oestrogen-synthesizing enzymes in each endometriotic site support the hypothesis of a tissue microenvironment that can both influence and be influenced by the expression of different oestrogenic pathways, locally affecting the availability of oestrogen needed for maintenance and progression of endometriotic lesions.